CT IMAGING FEATURES AND PATHOLOGICAL RESULTS OF PULMONARY INFLAMMATORY MYOFIBROBLASTIC TUMOR: AN ANALYSIS OF 28 CASES - LI Huijian, WANG Haitian, ZHOU Yu, WANG Guohua, SHI Huiwen (精准医学杂志, 2023)
Objective To investigate the CT imaging features and pathological results of pulmonary inflammatory myofibroblastic tumor, and to improve the awareness of this disease in clinical practice. Methods A retrospective analysis was performed for the clinical data, CT imaging features, and pathological results of 28 patients who were diagnosed with pulmonary inflammatory myofibroblastic tumor by surgery or lung biopsy. Results All 28 patients had a solitary lesion, among whom 21 had a lesion located in the left and right lower lobes of lungs. Plain CT scan showed inhomogeneous density of the lesion in 21 patients, lesions with smooth margins in 12 patients, and lesions with unsmooth margins in 16 patients, and contrast-enhanced CT scan showed obvious heterogeneous enhancement in 9 patients, flat sign in 12 patients, peach-tip sign in 7 patients, and long spiculation sign in 11 patients. Immunohistochemistry showed positive expression of Vimentin in 26 patients, SMA in 19 patients, ALK in 9 patients, CD-68 in 12 patients, and CD-99 in 9 patients and negative expression of CK in 14 patients, S-100 in 8 patients, and CD-34 in 13 patients. Conclusion The specific imaging findings of pulmonary inflammatory myofibroblastic tumor may help with early clinical diagnosis, and a combination of histopathology and immunohistochemistry is of great significance for prognostic eva-luation and postoperative diagnosis and treatment.